2021
DOI: 10.3390/molecules26237164
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Antifungal Activities and In Silico Studies of Natural Polyphenols from Some Plants

Abstract: A worldwide increase in the incidence of fungal infections, emergence of new fungal strains, and antifungal resistance to commercially available antibiotics indicate the need to investigate new treatment options for fungal diseases. Therefore, the interest in exploring the antifungal activity of medicinal plants has now been increased to discover phyto-therapeutics in replacement to conventional antifungal drugs. The study was conducted to explore and identify the mechanism of action of antifungal agents of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…According to literature, Mentha piperita L. is a great source of polyphenols [ 99 ]. Khanzada et al [ 100 ] reported that peppermint contained significantly higher amounts of phenolic compounds compared to other plants. It contains phenolic acids including hydroxybenzoic acids (protocatechuic, vanillic) and hydroxycinnamic acids (chlorogeic acid derivatives, rosmarinic, caffeic, p-coumaric, sinapic, caftaric, fertaric, and coutaric acid) as well as flavonoids: flavonols (kaempferol, quercetin, isorhamnetin derivatives), flavones (luteolin derivatives), flavanones (naringenin derivatives, hesperidin) and flavan-3-ols (epicatechin).…”
Section: Resultsmentioning
confidence: 99%
“…According to literature, Mentha piperita L. is a great source of polyphenols [ 99 ]. Khanzada et al [ 100 ] reported that peppermint contained significantly higher amounts of phenolic compounds compared to other plants. It contains phenolic acids including hydroxybenzoic acids (protocatechuic, vanillic) and hydroxycinnamic acids (chlorogeic acid derivatives, rosmarinic, caffeic, p-coumaric, sinapic, caftaric, fertaric, and coutaric acid) as well as flavonoids: flavonols (kaempferol, quercetin, isorhamnetin derivatives), flavones (luteolin derivatives), flavanones (naringenin derivatives, hesperidin) and flavan-3-ols (epicatechin).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the compounds such as 9,9-dimethoxybicyclo[3.3.1]nonane-2,4-dione-; 2,5-O Methylene-D-mannitol; Glycerol 1,2 diacetate; D-Glucitol, 1,4-anhydro; and 1,2,3-Propanetriol exhibited favorable characteristics like good corneal permeability, low molecular weight, and lipophilic qualities. According to Khanzada et al (2021) , there is a significant association between the antifungal phytochemicals of a plant and the target elements of fungal virulence. These authors emphasized the importance of identifying molecular targets and understanding their mode of antifungal activity, whether it involves competitive or allosteric inhibition, to develop innovative antifungal therapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that kaempferol and quercetin exhibit antifungal activity against C. parapsilosis and C. metapsilosis cultures following several pathways, notably the dysregulation of nucleic acid synthesis and the inhibition of cellular adhesion, affecting the development of the biofilms [ 152 ]. Molecular docking studies showed that quercetin had an increased affinity to bind 14α-demethylase and nucleoside phosphokinase enzymes, acting on a similar mechanism of azoles [ 153 ]. To complete the quercetin profile, Lotfi, M. et al studied its molecular effects after inclusion into a nanoemulsion vehicle.…”
Section: Biomaterials and Nanotechnological Approachesmentioning
confidence: 99%